2017
DOI: 10.5120/ijca2017915942
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Effects of Mobility Model on QoS in MANET

Abstract: As we know that in a Mobile Adhoc Network [MANET], mobility is the very important factor. Mobility gives the flexibility to the node to move in the coverage area. Here, in MANET multiple mobility models are proposed and every model provides different mobility and Quality of Service (QoS) support to the nodes. In this paper, we will present a study on these mobility models and its effects on QoS support in MANET and important findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…They observed that the movement of nodes is characterized based on mobility velocity. They found that the RWP has better results in suitable conditions than the other two models in such MANET environment, (5).…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the movement of nodes is characterized based on mobility velocity. They found that the RWP has better results in suitable conditions than the other two models in such MANET environment, (5).…”
Section: Introductionmentioning
confidence: 99%